A Novel Sequence: ZOOMit-Blood Oxygen Level-Dependent for Motor-Cortex Localization. Issue 2 (23rd October 2019) - Fang, Shengyu; Bai, Harrison X; Fan, Xing; Li, Shaowu; Zhang, Zhong; Jiang, Tao; Wang, Yinyan
Abstract: BACKGROUND: Use of conventional blood oxygen level-dependent functional magnetic resonance imaging (conventional-BOLD-fMRI) presents challenges in accurately identifying the hand-motor cortex when a glioma involves the ipsilateral hand-knob. Zoomed imaging technique with parallel transmission (ZOOMit)-BOLD is a novel sequence allowing high spatial resolution with a relatively small field of view that may solve this problem. OBJECTIVE: To compare the accuracy of ZOOMit-BOLD and conventional-BOLD in hand-motor cortex identification. METHODS: A total of 20 patients with gliomas involving the sensorimotor cortex were recruited to identify the hand-motor cortex by both ZOOMit-BOLD and conventional-BOLD. Based on whether the entire or partial glioma directly invaded (was located within) the hand-knob or indirectly affected it by proximity, patients were placed into the involved or uninvolved groups, respectively. Direct cortical stimulation was applied intraoperatively to verify the location of the hand-motor cortex. Overlap indices were used to evaluate the accuracy of the hand-motor cortex identification. An overlap index equal to 0, indicating lack of overlap, was classified as inaccurate classification. RESULTS: The accuracy of motor-cortex identification with ZOOMit-BOLD was 100% compared to only 65% with conventional-BOLD. The average overlap index yielded by ZOOMit-BOLD was higher than that of conventional-BOLD, regardless of whether gliomas directly invaded the hand-knob ( P  = .008) or not ( P  = .004). The overlap index in the involved group was significantly lower than that in the uninvolved group with both ZOOMit-BOLD ( P  = .002) and conventional-BOLD ( P  < .001). CONCLUSION: ZOOMit-BOLD may potentially replace conventional-BOLD to identify the hand-motor cortex, particularly in cases in which gliomas directly invade the hand-knob.